RNF19A inhibits bladder cancer progression by regulating ILK ubiquitination and inactivating the AKT/mTOR signalling pathway - Hao Deng; Guanghai Ji; Jun Ma; Jun Cai; Shaoping Cheng; Fan Cheng (Biology Direct)
Abstract Background The role of the RING finger protein superfamily in carcinogenesis has been widely studied, but one member of this family, RNF19A, has not yet been thoroughly explored in bladder cancer (BCa). Methods The expression levels of RNF19A in BCa samples and cell lines were analysed through data mining of public resources and further experiments. BCa cells in which RNF19A was stably overexpressed or knocked down were generated through lentivirus infection. The effects of RNF19A on cell proliferation, migration, and invasion were explored by performing a series of in vitro experiments, including CCK-8, colony formation, wound healing, and Transwell invasion assays. Using bioinformatics methods and multiple experiments, including western blot, qRT‒PCR, immunoprecipitation, cycloheximide, ubiquitination, and rescue assays, the mechanism underlying the effect of RNF19A on the progression of BCa was investigated. Results Here, we found that RNF19A expression was reduced in BCa samples and cell lines and that lower RNF19A expression predicted shorter overall survival of BCa patients. Functionally, forced expression of RNF19A suppressed BCa cell proliferation, migration, and invasion by inactivating the AKT/mTOR signalling pathway, whereas silencing RNF19A had the opposite effects. Mechanistically, RNF19A could directly interact with ILK and promote its ubiquitination and degradation. Rescue experiments revealed that forced ILK expression partially rescued the decreased phosphorylation of AKT, mTOR, and S6K1 caused by RNF19A overexpression and that the increased levels of the p-AKT, p-mTOR, and p-S6K1 proteins induced by RNF19A knockdown were eliminated after silencing ILK. Similarly, the effects of RNF19A overexpression or knockdown on the phenotypes of cell proliferation, migration, and invasion could also be restored by forced or decreased ILK expression. Conclusions RNF19A suppressed the proliferation, migration, and invasion abilities of BCa cells by regulating ILK ubiquitination and inactivating the AKT/mTOR signalling pathway. RNF19A might be a potential prognostic biomarker and promising therapeutic target for BCa.